Determining the landscape priority and their threats for the Critically Endangered Pongo tapanuliensis population in Indonesia - Dede Aulia Rahman; Dones Rinaldi; Wanda Kuswanda; Rondang Siregar; Fitri Noorch; Fahmi Hakim; Harnios Arief; Haryanto R Putro (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Rahman DE, Rinaldi D, Kuswanda W, Siregar R, Noor CF, Hakim F, Arief H, Putro HR. 2019. Determining the landscape priority and their threats for the Critically Endangered Pongo tapanuliensis population in Indonesia. Biodiversitas 20: 3584-3592. Understanding the habitat preference and spatial distribution for the management of medium-large primates is important for conserving and enhancing biodiversity in the most isolated and remote Batang Toru landscape, North Sumatra, Indonesia. Based on the first extensive orangutan survey dataset during 2000 and 2007, we aimed to provide microhabitat preference and distribution assessment for the new species of orangutan (Pongo tapanuliensis), a poorly known and threatened primate endemic in Indonesia. To inform future conservation measures, we develop a predictive habitat suitability map and use this map to show the current threat for Tapanuli orangutan in their habitat and as the basis of proposed of the landscape boundary in Batang Toru ecosystem. In order to identify some environmental factors affecting conservation, we analyzed the microhabitat preference of Tapanuli orangutan using maximum entropy modeling (MaxEnt). The modeled orangutan distribution map covers 1.458,06 km2 (58,52% of Batang Toru’s landscape) and reveals three distinct distribution areas. The four most important environmental predictors are the distance from the cultivation area, NDVI, mean precipitation, and distance from the secondary forest edge. The distribution of the orangutan overlap with land-use categories reveals that 42,98% of the distribution lies in protected areas, but that 15,54% lies in natural forest concessions and area for other purposes (APL). Large scale land-use masterplan is needed to provide strategies and control for future development in the possibility of land uses and management are allowed in the landscape including its conservation policies. Moreover, collaborative management strategies are needed to develop a sustainable management system. We confirmed the Batang Toru landscape as the sole of Indonesia’s biodiversity hotspots and a critical area to preserve the Tapanuli orangutan.